2021
DOI: 10.1002/adpr.202000122
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Blue Strong Microcavity Organic Light‐Emitting Diode Optimized by a Low Absorption Semitransparent Cathode and a Narrow Bandwidth Emitter

Abstract: Herein, deep blue strong microcavity top‐emitting organic light‐emitting diodes (TEOLEDs) optimized by a low absorbed silver cathode and a narrow bandwidth emitter are reported for realizing high‐efficiency and narrow spectral characteristics. Usually, the Mg:Ag cathode is widely used as a semitransparent cathode in TEOLED devices due to its favorable reflectivity and proper electron injection ability. However, the high extinction coefficient of Mg causes a decrease in the microcavity effect, causing a low opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…3−5 Unfortunately, such architectures often result in efficiency loss; therefore, the development of efficient emitters with narrow fwhm has become greatly important, and many researchers are eager to develop sharp emission of efficient emitters. 6,7 In general, the broad emission spectra are derived from participation of many vibronic transitions (v 0−n , n = 1, 2, 3...) between the ground state (S 0 ) and the excited state (S 1 ) with the inevitable structural variations. 8−10 According to the Franck−Condon principle, the vibronic coupling is negligible when the molecular structure of S 1 is nearly identical to that of S 0 , accompanied with only a v 0−0 vibronic transition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3−5 Unfortunately, such architectures often result in efficiency loss; therefore, the development of efficient emitters with narrow fwhm has become greatly important, and many researchers are eager to develop sharp emission of efficient emitters. 6,7 In general, the broad emission spectra are derived from participation of many vibronic transitions (v 0−n , n = 1, 2, 3...) between the ground state (S 0 ) and the excited state (S 1 ) with the inevitable structural variations. 8−10 According to the Franck−Condon principle, the vibronic coupling is negligible when the molecular structure of S 1 is nearly identical to that of S 0 , accompanied with only a v 0−0 vibronic transition.…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, the International Telecommunication Union (ITU) demonstrated the new color gamut of BT2020 for ultrahigh definition television (UHD TV), and the demand for high purity of the emission color has been increased in the organic light emitting diode (OLED) field. , In order to achieve the BT2020 standard of the blue region, the emitters are required to have deep blue emission of 460 nm with around 25 nm of full width at half-maximum (fwhm). Thus, broad electroluminescence (EL) spectra of organic luminescent materials require color filters or microcavity structures to satisfy the latest standard. Unfortunately, such architectures often result in efficiency loss; therefore, the development of efficient emitters with narrow fwhm has become greatly important, and many researchers are eager to develop sharp emission of efficient emitters. , In general, the broad emission spectra are derived from participation of many vibronic transitions ( v 0– n , n = 1, 2, 3...) between the ground state (S 0 ) and the excited state (S 1 ) with the inevitable structural variations. According to the Franck–Condon principle, the vibronic coupling is negligible when the molecular structure of S 1 is nearly identical to that of S 0 , accompanied with only a v 0–0 vibronic transition. Thus, suppressing the molecular structural deformation in the excited state and related vibronic coupling is crucial for achieving narrow fwhm emission. In 2016, Hatakeyama et al reported a new thermally activated delayed fluorescence (TADF) molecular framework based on alternatively positioned electron-deficient boron (B) and electron-rich nitrogen (N) atoms in a rigid skeleton, called the multiresonance (MR) structure .…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we have selected three different small molecule (SM) electron transport layer (ETL) materials such as 2,4bis(dibenzo[b,d]furan-2-yl)-6-phe-nyl-1,3,5-triazine (DDBFT), 1,3-bis(9-phenyl-1,10-phenanthrolin-2-yl) benzene (BPPB) and 2-[4-(9,10-di-naphthalen-2-yl-anthracene-2-yl)-phenyl]-1phenyl-1H-benzimidazole (ZADN). [28][29][30] The chemical structures of DDBFT, BPPB and ZADN were provided in Fig. S1.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have used a numerical approach to perform the spectrum at visible wavelengths and calculate the full width at half-maximum (FWHM) and central wavelength in the RGB structure in each situation of changing layer thickness or optical constant index [ 15 , 16 , 17 , 18 , 19 ]. Therefore, the thickness can be optimized based on the required optical characteristics.…”
Section: Introductionmentioning
confidence: 99%